DO INDEPENDENT COMMISSIONERS, GREEN INVESTMENTS, AND GREEN INNOVATION AFFECT ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG)? - Dwijayanti, Wulansari; Jayanti, Dwi (Finance and Banking Program, Accounting Department, Politeknik Negeri Semarang, 2024)
This study aims to test and analyze the influence of Independent Commissioners, Green Investments, and Green Innovation on the environmental, social, and governance (ESG) aspects of companies listed on the LQ45 Index of the Indonesia Stock Exchange during the period 2020-2022. The population in this study is 45 companies with a purposive sampling technique, resulting in a sample of 14 companies over a 3-year observation period. The data analysis technique used is multiple regression analysis using the IBM SPSS Statistics 26. The test results show that Independent Commissioners do not significantly influence the Environment, Social, and Governance. Green Investments have a positive and significant influence on the Environment, Social, and Governance. Meanwhile, Green Innovation has a positive and significant impact on the Environment, Social, and Governance. Together, Independent Commissioners, Green Investments, and Green Innovation can influence the Environment, Social, and Governance of LQ45 Index companies for the period 2020-2022.